2006
DOI: 10.1093/eurheartj/ehl328
|View full text |Cite
|
Sign up to set email alerts
|

Early complications of stenting in patients with congenital heart disease: a multicentre study

Abstract: After stenting, complications are common for congenital heart disease. The vast diversity of stenotic sites combined with relatively small patient populations makes these procedures sensitive to complications. Combining operator experience may reduce the risks of stenting in congenital heart disease. The availability of premounted stents for greater vessel diameters will likely reduce incidences of stent migration and embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Stent placement is generally considered the procedure of choice in pulmonary artery stenoses [2]. van Gameren et al reported complications from the use of stents in congenital heart disease in 2006, and found a major complication rate of 12% and 9% from stenting of the left and right pulmonary arteries, respectively [3]. Out of 126 patients who underwent pulmonary artery stenting, one patient, an 11-year-old female with postoperative tetralogy of Fallot with branch pulmonary stenosis, developed fatal left ventricular dysfunction following coronary ischemia because of RPA stent compression of the LMCA.…”
Section: Discussionmentioning
confidence: 99%
“…Stent placement is generally considered the procedure of choice in pulmonary artery stenoses [2]. van Gameren et al reported complications from the use of stents in congenital heart disease in 2006, and found a major complication rate of 12% and 9% from stenting of the left and right pulmonary arteries, respectively [3]. Out of 126 patients who underwent pulmonary artery stenting, one patient, an 11-year-old female with postoperative tetralogy of Fallot with branch pulmonary stenosis, developed fatal left ventricular dysfunction following coronary ischemia because of RPA stent compression of the LMCA.…”
Section: Discussionmentioning
confidence: 99%
“…One should always be aware that a coronary artery may originate from purely posterior to lateral, and that any stenting of the area ranging from the main pulmonary trunk distal to where the right pulmonary artery crosses the ascending aorta, may compress a coronary artery [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of early complications related to PA stenting was about 16.6% total and 6.2% for major complications [12].…”
Section: Commentmentioning
confidence: 99%
“…It is important to mention that only 58% of patients in this series had interventions on the lobar or segmental PA (ie, peripheral PA), while the remaining 42% of the patients received only central PA interventions. Unfortunately, most of the published studies for transcatheter therapy for PAS combine the data for central and peripheral PA interventions as 1 group [9][10][11][12][13][14][15][16]. We believe that the use of a classification system to stratify the data based on the level of intervention performed is essential to enable objective comparison of data from various groups and different interventions.…”
Section: Commentmentioning
confidence: 99%